2012
DOI: 10.2151/sola.2012-030
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength Dependence of Refractive Index of Secondary Organic Aerosols Generated during the Ozonolysis and Photooxidation of α-Pinene

Abstract: Atmospheric aerosol particles play an important role in climate change by scattering and absorbing solar radiation. To quantify the direct influence of aerosols on the atmospheric radiation balance, a detailed understanding of the complex refractive index (RI) for a variety of aerosols is required. The wavelength dependence of the RI values for secondary organic aerosols (SOAs) generated during the ozonolysis and photooxidation of α-pinene, which is a major biogenic volatile organic compound (BVOC), was invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
64
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(76 citation statements)
references
References 29 publications
10
64
2
Order By: Relevance
“…Figure 9 shows that the real part of the CRI decreases substantially as the O : C of the bulk SOA decreases. This trend is in agreement with the positive correlation between the extinction coefficient at 532 nm wavelength and O : C observed by for the heterogeneous OH oxidation of squalane and aze- (Nakayama et al, 2012) -pinene (Lambe et al 2013) toluene (Nakayama et al, 2013) 1 naphtalene (Lambe et al 2013) guaiacol (Lambe et al 2013) tricyclo[5.2.1.0 2,6 ]decane (Lambe et al 2013) squalane azelaic acid Photooxidation Ozonolysis OH-oxidation laic acid particles. Nakayama et al (2013) reported an increasing real part of the CRI at 532 nm with increasing O : C for SOA generated from the photooxidation of toluene.…”
Section: Dependence Of the Cri And Gf On The Chemical Compositionsupporting
confidence: 89%
See 2 more Smart Citations
“…Figure 9 shows that the real part of the CRI decreases substantially as the O : C of the bulk SOA decreases. This trend is in agreement with the positive correlation between the extinction coefficient at 532 nm wavelength and O : C observed by for the heterogeneous OH oxidation of squalane and aze- (Nakayama et al, 2012) -pinene (Lambe et al 2013) toluene (Nakayama et al, 2013) 1 naphtalene (Lambe et al 2013) guaiacol (Lambe et al 2013) tricyclo[5.2.1.0 2,6 ]decane (Lambe et al 2013) squalane azelaic acid Photooxidation Ozonolysis OH-oxidation laic acid particles. Nakayama et al (2013) reported an increasing real part of the CRI at 532 nm with increasing O : C for SOA generated from the photooxidation of toluene.…”
Section: Dependence Of the Cri And Gf On The Chemical Compositionsupporting
confidence: 89%
“…Recently, Flores et al (2014) showed that the real part of the CRI at 405 nm is positively correlated to the O : C for a mixture of biogenic VOC (α-pinene and limonene) and biogenic VOC mixture with subsequent addition of an anthropogenic VOC (p-xylene-d 10 ). On the other hand, an opposite trend was observed by Nakayama et al (2012) with a decrease of the real part of the CRI at 532 nm wavelength with increasing O : C for SOA produced from the ozonolysis and photooxidation of α-pinene. Lambe et al (2013) studied SOA formed by OH oxidation of various gas-phase precursors (naphthalene, tricyclo[5.2.1.0 2,6 ]decane, guaiacol and α-pinene) and retrieved a decreasing real part of the CRI with increasing oxidation.…”
Section: Dependence Of the Cri And Gf On The Chemical Compositionmentioning
confidence: 89%
See 1 more Smart Citation
“…The β-pinene mixing ratios (15 ppb) and the resulting aerosol mass concentrations (30 to 40 µg m −3 ) in this work were low compared to other monoterpene SOA refractive index studies (Kim et al, 2010;Nakayama et al, 2010Nakayama et al, , 2012Lambe et al, 2013). Kim and Paulsen (2013) note that high-aerosol mass loadings are likely to result in proportionally more high-volatility species in the particle phase, and are thus less representative of ambient aerosols which have lower volatility constituents.…”
Section: Discussionmentioning
confidence: 53%
“…a-Pinene SOA has little absorbing effect in all wavelengths and a refractive index of 1.44 at 532 nm is recommended by Kim and Paulson (2013). Wavelength dependence of RI is studied by Nakayama et al (2012) and Yu et al (2008), and both results come to a conclusion that RI will decrease with increasing wavelength. Linear polynomial fitting is done for the data listed in Table 2, and 1.48 and 1.42 are recommended for 350 and 700 nm BSOA refractive index, respectively.…”
Section: Soa Optical Parametersmentioning
confidence: 99%